Analisis Kebutuhan Guru terhadap Integrasi Nilai Moderasi Beragama dalam Materi Ajar Bahasa Inggris - Yulnetri, Yulnetri; Novita, Yona; Rahmawati, Rahmawati; Khairat, Annisaul (AS-SABIQUN, 2024)
This research aims at figuring out teachers and students’ need of integrated religious moderation in English materials at Madrasah Tsanawiyah (Islamic Junior High School) grade 7. This was a descriptive research conducted in four different Madrasah in West Sumatera, i.e., MtsN Batusangkar, MtsN Sawah Lunto, MtsN Solok, dan MtsS Muhammadiyah Payakumbuh . The informants were four English teachers at grade 7 were interviewed in order to gain the data about their needs of integrated religious moderation values in English materials, and 121 students who filled the questionnaire sent via Google form. The result shows that all of the informants demand the integrated religious moderation values, in terms of national commitment, tolerant, nonviolent, and accommodative to local culture, in English materials at grade 7 of Madrasah Tsanawiyah in West Sumatera. Then, the topics potential to be integrated are Apologizing, Introducing self, Descriptive text and Warning.